2012
DOI: 10.1111/j.1476-5381.2012.01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Luminal cholinergic signalling in airway lining fluid: a novel mechanism for activating chloride secretion via Ca2+‐dependent Cl and K+ channels

Abstract: BACKGROUND AND PURPOSERecent studies detected the expression of proteins involved in cholinergic metabolism in airway epithelial cells, although the function of this non-neuronal cholinergic system is not known in detail. Thus, this study focused on the effect of luminal ACh as a regulator of transepithelial ion transport in epithelial cells. EXPERIMENTAL APPROACHRT-PCR experiments were performed using mouse tracheal epithelial cells for ChAT and organic cation transporter (OCT) transcripts. Components of trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 63 publications
6
25
0
2
Order By: Relevance
“…4 However, M1R-mRNA was not detected in Type II taste cells and no negative cholinergic feedback loop was found. Consistent with previous reports, 15,16,46 we have observed that MC is regulated by ACh and that this ACh-induced increase in cilia-driven PTS is M3Rdependent. 38 Thus, this negative regulation seems to be specific for the nontaste organs but the involved MR are organ-specific.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…4 However, M1R-mRNA was not detected in Type II taste cells and no negative cholinergic feedback loop was found. Consistent with previous reports, 15,16,46 we have observed that MC is regulated by ACh and that this ACh-induced increase in cilia-driven PTS is M3Rdependent. 38 Thus, this negative regulation seems to be specific for the nontaste organs but the involved MR are organ-specific.…”
supporting
confidence: 93%
“…[4][5][6][7][8] Based on the recent advances in single-cell RNA-sequencing it became evident that more than one BC type exists in the airways and BC signature varies in different organs. [14][15][16][17] In the human upper airways nitric oxide released in response to taste receptor (TasR) stimulation increases ciliary beat, [18][19][20][21] but there is no proof that the same mechanism operates in the lower airways or additional mechanisms are influencing MC. 7,12 Yet, it remains elusive if these cells indeed synthesize and release ACh.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ACh stimulates the ciliary beat frequency and particle transport speed at the tracheal surface via the M3 subtype of muscarinic receptors in the murine trachea [49]. It is also likely that ACh released into the lumen contributes to the activation of transepithelial ion currents and fluid secretion by luminal ACh receptors as was shown recently for tracheal epithelial cells [50,51]. Consistent with this, bitter substances were found to increase the anion transport and fluid secretion in the rat colon [52].…”
Section: Discussionsupporting
confidence: 50%
“…; Hollenhorst et al . ). In both lung cancer and colon cancer, ACh acts as an autocrine growth factor for cancer growth and development (Song et al .…”
mentioning
confidence: 97%